2000
DOI: 10.1128/aac.44.2.450-452.2000
|View full text |Cite
|
Sign up to set email alerts
|

Failure of Short-Course Ceftriaxone Chemotherapy for Multidrug-Resistant Typhoid Fever in Children: a Randomized Controlled Trial in Pakistan

Abstract: The precise duration of therapy of multidrug-resistant (MDR) typhoid with broad-spectrum cephalosporins is uncertain. We prospectively randomized 57 children with culture-proven MDR typhoid to receive treatment with intravenous ceftriaxone (CRO) (65 mg/kg of body weight/day) for 7 days (short course; n ‫؍‬ 29) or 14 days (conventional; n ‫؍‬ 28). The response to therapy, as evaluated by the serial monitoring of the typhoid morbidity score and bacteriological clearance, was comparable between groups. In contras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 20 publications
1
25
0
Order By: Relevance
“…The slightly lower cure rate in this study compared with those in these other studies may be due to the higher doses of azithromycin used in the other studies. The response to azithromycin in this study compares favorably with the results reported for ceftriaxone and cefixime when given for 7 days for uncomplicated enteric fever (5,9,18,19,36).…”
Section: Discussionsupporting
confidence: 73%
“…The slightly lower cure rate in this study compared with those in these other studies may be due to the higher doses of azithromycin used in the other studies. The response to azithromycin in this study compares favorably with the results reported for ceftriaxone and cefixime when given for 7 days for uncomplicated enteric fever (5,9,18,19,36).…”
Section: Discussionsupporting
confidence: 73%
“…Ceftriaxone may be administered both intravenously and intramuscularly, typically for five days; but a two-day course has also been shown to be effective for shigellosis [93], but not for typhoid fever, which needs longer regimens [94]. Additionally, the clinical resolution of symptoms is typically slower with ceftriaxone than with ciprofloxacin, and more severe cases may require courses longer than five days.…”
Section: Third Generation Cephalosporinsmentioning
confidence: 99%
“…Ceftriaxone recorded a sensitivity of 93.75%. Presently, resistance to third generation cephalosporin has also been reported by Bhutta ZA et al 22 .…”
Section: Resultsmentioning
confidence: 96%